Preventing Enamel Demineralization Using Propolis Fluoride and Sodium Fluoride Varnishes: A Comparison - Aprillia, Iffi; Ricardo, Shalina; Setiadi, Kevin Elim (Journal of Indonesian Dental Association, 2021)
Introduction: Soft drink are one of the most frequently consumed beverages that can cause enamel demineralization, with a pH ranging from 1 to 4. The use of fluoride varnishes in clinical dentistry is the most common and favored method of countering this process, and the newest innovation made from natural substances is propolis fluoride. Objective: To compare the enamel structures of samples treated with propolis fluoride and sodium fluoride after being demineralized by carbonated liquid. Methods: Twenty-seven permanent premolar teeth were equally divided into three groups for treatment. One group received propolis fluoride, one received sodium fluoride, and the control group was not treated. The samples were exposed to 5% acetic acid for 20 minutes and subsequently varnished with fluoride. The samples were then exposed to Fusayama’s artificial saliva for 30 minutes, followed by a carbonated liquid for 1 hour. The samples were analyzed with an EDX or the quantitative analysis and a SEM was used to photograph the surfaces of all the samples to compare them qualitatively. Results: The percentage of the fluoride element inside the enamel surfaces from the EDX showed no significant differences between any of the groups (P ≥ 0.05), although the control group showed differences in the enamel surface structure compared to the other groups. Conclusion: Propolis fluoride and sodium fluoride have the same effectivity in inhibiting enamel demineralization by carbonated drinks.